Factors affecting canine fecal and parasitic contamination of public green spaces of Buenos Aires city, Argentina, and visitors’ perception of such contamination - Rubel, Diana (2019)
Canine fecal contamination in public green areas is difficult to control. Our objectives were to assess: (i) the relationship between fecal contamination in public green spaces of Buenos Aires (Argentina) and the type of green space (boulevard/square/park), considering their area, presence/absence of control measures, and human population density in the surroundings (high or low); (ii) the perception of people of such contamination and (iii) the frequency of parasites in dog feces. In each green space (n = 26), feces were counted in thirty 25-m2 plots randomly located. The opinion survey consisted of asking people (358) what their perception of fecal contamination was, whether it bothered them and whether they thought it was hazardous to the dogs' or people' health. Canine fecal samples randomly collected (n = 112) were concentrated and examined microscopically. Mixed-effect generalized linear models were fitted to evaluate the effect of selected variables on fecal contamination. People's perception of human and canine health risks were assessed by logistic regression. Canine fecal contamination was lower in squares with control measures and in parks with control measures located in densely populated areas, and higher in boulevards located in densely populated areas. The visitor's perception was that feces were associated with dirtiness (77%) and odor (30.8%). Parasites were detected in 51.8% of fecal samples. Our results confirm that environmental control measures decrease canine fecal contamination of public green spaces, and that more than 65% of the people interviewed do not relate fecal contamination to risks to human/dog health.